Accounting, power, and emancipation: A systematic literature review of critical accounting perspectives - Nadhila Latifah; Ahmad Sobari; Adelia Noviyanti; Bukar Isa Gamara (PT Bina Perfidia Akademia, 2026)
Accounting is increasingly viewed not merely as a technical reporting mechanism but as a social practice shaped by power relations and ideological interests. This study aims to analyze the critical accounting paradigm as an emancipatory instrument in contemporary accounting practice. The research employs a Systematic Literature Review (SLR) using an interpretative approach to examine ten scholarly articles obtained from reputable databases. The findings indicate that critical accounting challenges the assumption of neutrality in accounting by highlighting its role in constructing, legitimizing, and contesting social realities. The literature reveals three major themes: power relations embedded in accounting practices, emancipatory efforts through alternative and participatory forms of accountability, and epistemological reflection on the production of accounting knowledge. This study contributes to the development of critical accounting discourse by demonstrating how accounting can move beyond technical and compliance-oriented functions toward a more ethical, reflective, and socially transformative practice that promotes justice, sustainability, and epistemic pluralism. Abstrak Akuntansi semakin dipahami tidak hanya sebagai mekanisme pelaporan teknis, tetapi juga sebagai praktik sosial yang dibentuk oleh relasi kekuasaan dan kepentingan ideologis. Penelitian ini bertujuan menganalisis paradigma akuntansi kritis sebagai instrumen emansipatoris dalam praktik akuntansi kontemporer. Penelitian menggunakan metode Systematic Literature Review (SLR) dengan pendekatan interpretatif terhadap sepuluh artikel ilmiah yang diperoleh dari basis data bereputasi. Hasil penelitian menunjukkan bahwa akuntansi kritis menolak asumsi netralitas akuntansi dengan menyoroti perannya dalam membentuk, melegitimasi, dan menantang realitas sosial. Literatur yang dikaji mengungkap tiga tema utama, yaitu relasi kekuasaan dalam praktik akuntansi, upaya emansipatoris melalui bentuk akuntabilitas yang partisipatif dan alternatif, serta refleksi epistemologis mengenai konstruksi pengetahuan akuntansi. Penelitian ini berkontribusi pada pengembangan wacana akuntansi kritis dengan menunjukkan bahwa akuntansi dapat melampaui fungsi teknis dan kepatuhan menuju praktik yang lebih etis, reflektif, dan transformatif guna mendukung keadilan sosial, keberlanjutan, dan pluralisme epistemik.